Occurrence and Risk Factors of Dog Bites in Northern Indigenous Communities: A Scoping Review - Daigle, Laurence; Delesalle, Léa; Ravel, André; Ford, Barrie; Aenishaenslin, Cécile (Frontiers in Veterinary Science, 2022)
The relationship between northern Indigenous people and dogs has evolved over the past years alongside events such as colonization, settlement, proliferation of snowmobiling and other socio-cultural and environmental changes. These changes have had negative impacts on this relationship, and with the endemic presence of arctic fox rabies, dog bites have become an important public health burden. The objective of this study was to synthesize the state of knowledge regarding the occurrence of dog bites and associated risk factors in the specific context of northern Indigenous communities. A scoping review was conducted in seven bibliographic databases, from June 2018 to May 2020. From this search, 257 original studies were identified and eight papers were included for final analysis. Annual occurrence of dog bites in northern Indigenous communities ranged from 0.61 to 59.6/10,000 inhabitants. Dog bites affected 27 to 62.9% of the population in those regions during their lifetime. Very few studies compared the occurrence of dog bites between people living in northern communities with other populations or settings, but available evidence suggests that Indigenous people living in northern communities are at higher risk of dog bites than the rest of the population. Several individual and environmental risk factors were identified in the selected studies, although the strength of evidence varied significantly. Age (children) and gender (male) were well documented individual risk factors. Other factors, such as organizational barriers to dog management and lack of access to veterinary services, were identified and discussed by several authors. The results of this study support concerns about the higher risk of bites in northern Indigenous communities, and underscore the urgent need for more research into the contextual and environmental factors that impact the mitigation of these risks.